DESAFIOS CONTEMPORÂNEOS NO DIAGNÓSTICO E TRATAMENTO DO TRANSTORNO DO DÉFICIT DE ATENÇÃO COM HIPERATIVIDADE (TDAH) - Neves , Sara Izabel Cargnin Henrique; Farinon, Matheus Lobato; Coronel, Luiz Carlos Illafont (Brazilian Journal of Implantology and Health Sciences, 2024)
Attention Deficit/Hyperactivity Disorder (ADHD) is a complex disorder that requires comprehensive diagnosis, treatment and support for the child and family. The aim is to overcome challenges and improve academic, social and emotional performance. Awareness and adequate resources are vital for the well-being of affected children and their families. This study aimed to understand the current challenges in diagnosing and treating ADHD. To achieve this, a systematic literature review was carried out, following the guidelines of the PRISMA protocol. The Medline, Lilacs and Scielo databases were searched, using specific criteria for the inclusion or exclusion of relevant information. The main conclusion of this study is the need for flexible and collaborative approaches to the diagnosis and treatment of ADHD. The study recognizes the complexity inherent in this condition and highlights the importance of a more refined and individualized approach in the therapeutic decision-making process. It points out that the standardization of treatment is often hampered by factors such as the severity of symptoms, the presence of comorbidities and the availability of resources, as well as the need to include the preferences of users and family members from the outset to ensure more effective management of ADHD.